Catalyst for the reduction of NO to N2 with ethanol or ethanol and hydrogen under lean DENOx conditions - (:unkn) unknown (My University, 2010)
The invention relates to a novel catalyst having excellent activity, selectivity and stability for reducing nitric oxide to gas nitrogen, with ethanol or an ethanol-hydrogen mixture being used as a reducing agent, in the low temperature range of 150-300 °C and in the presence of an excess of oxygen (e.g., 5 % vol), H2O (5 % vol) and SO2 (50 ppm) in the supply. The inventive catalyst consists of silver crystals which are in contact with the phases of a mixed MgO, CeO2 and Al2O3 medium. The Ag/MgO-CeO2-Al2O3 catalyst can be used to obtain NO conversion levels which are greater than 40 %, nitrogen selectivity values of greater than 95 % and CO2 selectivity values greater than 97% under NOx oxidation conditions in the 150-400 °C temperature range and for a surface contact time of 0.09 s. In particular, 90% NO conversion is obtained as well as N2 and CO2 selectivity levels of 99 % at 250 °C with a reaction mixture of 500 ppm NO/1000 ppm C2H5OH /5% O2 /5% H2O / 50ppm SO2/He:
Keywords: Catalyst; B01J23/66 Silver or gold; Nitric oxide; Gas nitrogen; Silver crystals